2022
DOI: 10.3390/ijms23169082
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Underlying the Cardioprotective Role of Allicin on Cardiovascular Diseases

Abstract: Cardiovascular diseases (CVDs) are a group of diseases in which the common denominator is the affection of blood vessels, heart tissue, and heart rhythm. The genesis of CVD is complex and multifactorial; therefore, approaches are often based on multidisciplinary management and more than one drug is used to achieve the optimal control of risk factors (dyslipidemia, hypertension, hypertrophy, oxidative stress, endothelial dysfunction, inflammation). In this context, allicin, a sulfur compound naturally derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 106 publications
0
21
0
Order By: Relevance
“…A weakness of this review is that we did not focus on evaluating the side effects, toxicity, safety, and effectiveness of these treatments with sulfur compounds so they can be used in clinical research. However, it has been reported that garlic compounds could be a therapy with fewer side effects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A weakness of this review is that we did not focus on evaluating the side effects, toxicity, safety, and effectiveness of these treatments with sulfur compounds so they can be used in clinical research. However, it has been reported that garlic compounds could be a therapy with fewer side effects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These sulfides correspond to diallyl sulfide (DAS), diallyl disulfide (DADS), diallyl trisulfide (DATS), methyl allyl disulfide (MADS), methyl allyl sulfide (MAS), ajoene, and vinyl dithiins (2-vinyl-1,3-dithiin, 3-vinyl-1,2-dithiin). The water-soluble garlic compounds are SAC, S-allylmercapto-l-cysteine (SAMC), and S-methyl cysteine [ 8 ].…”
Section: Garlicmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, garlic ( Allium sativum ) is a spice rich in sulfur compounds, several of which have shown favorable effects in various diseases, including cardiovascular ( Anaeigoudari, Safari & Khazdair, 2021 ; Sánchez-Gloria et al, 2022 ; Sharma & Rani, 2023 ). Diallyl thiosulfinate (allicin) is a sulfur compound in garlic, which is the main component formed when garlic is macerated or crushed ( Sánchez-Gloria et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, garlic ( Allium sativum ) is a spice rich in sulfur compounds, several of which have shown favorable effects in various diseases, including cardiovascular ( Anaeigoudari, Safari & Khazdair, 2021 ; Sánchez-Gloria et al, 2022 ; Sharma & Rani, 2023 ). Diallyl thiosulfinate (allicin) is a sulfur compound in garlic, which is the main component formed when garlic is macerated or crushed ( Sánchez-Gloria et al, 2022 ). Recently, several studies have shown that allicin has multiple beneficial effects, including antioxidant, immunomodulatory, antidiabetic, antihypertensive, cardioprotective, and nephroprotective ( El-Sheakh et al, 2016 ; García-Trejo et al, 2017 ; Liu et al, 2010 ; Arellano-Buendía et al, 2018 , 2020 ; Sánchez-Gloria et al, 2021 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%